Short Note: 2022 Hunga Tonga-Hunga Ha'apai tsunami measured beneath the Ross Ice Shelf - Stewart, Craig; Horgan, Huw Joseph; id_orcid:0 000-0002-4836-0078; Stevens, Craig (Cambridge University Press, 2024)
On 15 January 2022, 04h:15 UTC, the volcano Hunga Tonga-Hunga Ha'apai in the south-west Pacific Ocean (20°32'32.37''S, 175°23'38.67''W) erupted in what proved to be the most powerful such event since Krakatau in 1883. Among the many impacts of the eruption, a substantial tsunami propagated throughout the south-west Pacific Ocean. The signatures of the eruption were recorded at a wide range of recording stations globally, including the atmospheric pressure wave, the tsunami itself and, in addition, higher-order responses, such as a tsunami associated with the pressure wave (Carvajal et al. 2022). ISSN:0954-1020 ISSN:1365-2079